The Russian-Language Version of the HOOS Questionnaire for Assessing Hip Joint Condition: Cross-Cultural Adaptation, Validation, and Testing - Anzhela S. Mulyk; Tatiana I. Ionova; Tatiana P. Nikitina; Anton A. Akulaev; Aleksandr V. Gubin (Travmatologiâ i Ortopediâ Rossii)
Background. Patient-reported outcomes (PRO) play a significant role in interpreting treatment results. The HOOS is a popular patient-completed questionnaire used to assess hip joint function and quality of life. To date, there is no official Russian version of HOOS that has undergone all the language adaptation and validation procedures.